2021
DOI: 10.1177/00368504211036319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the characteristics of outpatient and emergency diseases in the department of otolaryngology during the “COVID-19” pandemic

Abstract: The pandemic of “Corona Virus Disease 2019” (COVID-19) has changed the lives of people. There have been changes in common outpatient and emergency cases in otolaryngology, so an analysis of data pertaining to this was completed. This study is to evaluate the impact of viral infection disease in otolaryngological common disease. This study uses the data of common diseases in the outpatient and emergency department during the “COVID-19” pandemic (from February to April 2020) and the same period in the past 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…A study from Turkey found an increased incidence of SSNHL during the COVID-19 epidemic, with 60.3% of subjects having signs compatible with COVID-19 ( 18 ). A large tertiary hospital in China also found an increase in SSNHL visits to the outpatient and emergency departments during the COVID-19 pandemic compared to the past ( 19 ). However, several studies found no increase in the incidence of SSNHL after the COVID-19 outbreak, concluding that SARS-CoV-2 does not appear to have a significant risk of SSNHL development ( 20 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study from Turkey found an increased incidence of SSNHL during the COVID-19 epidemic, with 60.3% of subjects having signs compatible with COVID-19 ( 18 ). A large tertiary hospital in China also found an increase in SSNHL visits to the outpatient and emergency departments during the COVID-19 pandemic compared to the past ( 19 ). However, several studies found no increase in the incidence of SSNHL after the COVID-19 outbreak, concluding that SARS-CoV-2 does not appear to have a significant risk of SSNHL development ( 20 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the 119 hospitalized SARS-CoV-2-PCR-positive patients, tinnitus comprised 11% of otolaryngological complaints ( 10 ). In addition, during the pandemic, it was observed that significantly more patients sought professional help for tinnitus in tertiary healthcare institutions than before the pandemic ( 11 ). In a large UK-based survey-based study that enclosed 6,881 subjects with a sub-sample of 1,274 individuals who had tinnitus prior to the pandemic, tinnitus worsened significantly more in those who contracted COVID-19 than in the non-infected ones.…”
Section: Introductionmentioning
confidence: 99%
“…Mustafa ( 2020 ), however, highlighted that the lack of significant COVID-19 symptoms does not necessarily provide assurance that cochlear function is healthy and safe. Several studies reviewed indicate the presence of SSNHL with or without tinnitus and vertigo (Beckers et al, 2021 ; Chern et al, 2021 ; Gallus et al, 2021 ; Jin et al, 2021 ; Kimura et al, 2021 ; Korkmaz et al, 2021 ; Koumpa et al, 2020 ; Munro et al, 2020 ; Ricciardiello et al, 2021 ) with nonspecific symptoms such as SSNHL being reported as possibly being the sole feature that could be used to identify a COVID-19 case (Kilic et al, 2020 ). The reported rate of otological or vestibular symptoms varied significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, as COVID-19 is a viral infection, prompt diagnosis of hearing impairment is critical because prompt treatment of viral-induced hearing loss has been proven to yield positive outcomes, while unidentified or late-identified permanent hearing impairment has well-documented negative impacts on the quality of life of the individuals affected (Saniasiaya, 2021 ). Interestingly, Jin et al ( 2021 ) also reported that quality of life has been impacted by COVID-19 by raising mental-related disease patients of the otolaryngology department (e.g. panic, anxiety, depression and sleep disorders).…”
Section: Introductionmentioning
confidence: 99%